Chronic Encapsulated Expanding Thalamic Hematoma Associated with Obstructive Hydrocephalus following Radiosurgery for a Cerebral Arteriovenous Malformation: A Case Report and Literature Review. (24th January 2016) - Takei, Jun; Tanaka, Toshihide; Yamamoto, Yohei; Teshigawara, Akihiko; Tochigi, Satoru; Hasegawa, Yuzuru; Murayama, Yuichi
Abstract : Chronic encapsulated intracerebral hematoma is a unique type of intracerebral hematoma accompanied by a capsule that is abundant in fragile microvasculature occasionally causing delayed regrowth. A 37-year-old man who had undergone radiosurgery for an arteriovenous malformation (AVM) causing intracerebral hematoma in the left parietal lobe presented with headache, vomiting, and progressive truncal ataxia due to a cystic lesion that had been noted in the left thalamus, leading to progressive obstructive hydrocephalus. He underwent left frontal craniotomy via a transsylvian fissure approach, and the serous hematoma was aspirated. The hematoma capsule was easy to drain and was partially removed. Pathological findings demonstrated angiomatous fibroblastic granulation tissue with extensive macrophage invasion. The concentration of vascular endothelial growth factor (VEGF) was high in the hematoma (12012 pg/mL). The etiology and pathogenesis of encapsulated hematoma are unclear, but the gross appearance and pathological findings are similar to those of chronic subdural hematoma. Based on the high concentration of VEGF in the hematoma, expansion of the encapsulated hematoma might have been caused by the promotion of vascular permeability of newly formed microvasculature in the capsule.